Self-assembling peptide hydrogel: design, characterization and application - Huang, Hongzhou (Kansas State University, 2014)
Rational design of peptide molecules to undergo spontaneous organization as a higher-ordered supramolecular structure is an attractive and fast-growing field for developing new functional biomaterials. Hydrogel, with its high water content and three-dimensional architecture, is formed by a self-assembling peptide and has great potential for broad biomedical applications. The key challenge in controlling the functional properties of final biomaterials can be met by designing the peptide primary structure carefully at the beginning and developing a comprehensive understanding of peptide self-assembly pathways. In this study, we first designed a Ca2+ responsive peptide (eD2) using identified functional native domains from a spider flagelliform silk protein and the Ca2+ binding domain of lipase Lip A from Serratia marcescens. Instead of directly linking the two peptide sequences, we rationally inserted the ion-binding motif into the silk structure sequence and made the new peptide inherit the physical characteristics of both model sequences and assemble into nanofibers when triggered by Ca2+. Next, we introduced the amphiphilic property to the eD2 peptide by conjugating its N-terminus with a strong hydrophobic sequence from a trans-membrane segment of human muscle L-type calcium channel. This self-assembly peptide, called h9e, was responsive to Ca2+, solution pH, and selected proteins for hydrogel formation. Interestingly, the turning segment GSII of h9e was considered to play a critical role in construction of the finial matrix. This hypothesis was further demonstrated by exploiting a series of amphiphilic diblock model peptides with different conformational flexibility. The kinetic rate of peptide assembly was suggested as one of the key influences for peptide supramolecular assembly morphology. To better understand the peptide self-assembly process during hydrogel formation, the conformational, morphological, and mechanical properties of h9e molecules in different dimethylsulfoxide/H2O solutions were monitored by 1D and 2D proton nuclear magnetic resonance (NMR), electron microscopy, and a rheometer. The h9e peptide hydrogel formed with Ca2+ and albumin exhibited superior physiological and specific injectable properties, which provides a more realistic tool for 3D cell culture and drug delivery. This study generates new knowledge and contributes to the field by leading to a better understanding the self-assembly hydrogel formation and designing peptides with unique properties for biomedical applications such as cell culture, drug delivery, and tissue engineering.
Keywords: Peptide; Self-assembly; Recovery; Hydrogel; Shear-thinning; Biochemistry (0487); Biomedical Engineering (0541)